Analysis of Planetary Mechanism Flow-solid Coupling of the Cutting Department of the Shearer based on SPH Method - Lijuan Zhao; Wen Zhang; Bo Zhang (Jixie chuandong)
The planetary mechanism of shearer cutting department operates in harsh environment， suffers heavy impact load and complicated internal lubrication. In order to calculate the dynamic characteristics of planetary mechanism more accurately， a Smoothed Particle Hydrodynamics （SPH） method based on Abaqus is put forward. Taking MG400/951WD shearer as the engineering object， the three-dimensional assembly model of shearer is established by three-dimensional modeling software Pro/E， which is imported into Adams for multi-body dynamics simulation and output load file. The fluid-solid coupling model of planetary mechanism is established in Abaqus， and the dynamic analysis of non-linear gear meshing is carried out by using explicit dynamics solver， which verifies that the oil meshless feature has natural advantages over traditional dynamic analysis method and can be widely used in the dynamic study of key structural parts of industrial and mining equipment.